O papel do profissional de responsabilidade social empresarial, seus referenciais e desafios - Alexandre, Maria de Fátima Duque Caçador (2008)
Corporate Social Responsibility gains inedited prominence in history. The transformations brought or evidenced by globalization contribute for modifications in the understanding of the economic agents roles and in the models of companies relationship with society. The linear understanding that the companies role is only to provide interest for shareholders, begins to be replaced by a discussion which considers the complexity of current context, with all interactions, interdependences and potential of impact of the participative elements. After the II World War the creation of ONU made easier the creation of the first instruments of international regulation and today we have some great humanity agreements on human rights, labor rights, and environment protection among others. A number of conventions, treaties, certifications and agreements, national and international, were found, which try to guide and ensure the socially responsible behavior of the organizations in general and specifically of the companies. In this dissertation, it is presented the evolution of the understanding on corporate social responsibility, and how the concepts of ethic and sustainable development were incorporated into it. In the sequence of the work, the 33 sources of references considered more outlined for the practice of social responsibility in the organizations are mentioned. The advance of the requirements standardization and the expectation of changing of companies relationship with society made them to develop projects within this context and also enabled the arising of social responsibility professionals dedicated exclusively, in some cases and in another, employees partially dedicated, who accumulate activities of this area with other. With the purpose of knowing the reality of the corporate social responsibility professional role, surveys and interviews were carried out to identify how the active professionals see their role in the organization, the tools and reference that they use and main challenges that they face. As it is a new career, in an area also recent and with a theoretical structure still in development, it is intended to contribute for a discussion, which is still in its beginning, about the significant role of the professional that takes on these activities in a company. From the analysis of the concept evolution and survey results, the challenges and the opportunities that have been found and the competences requested by this new professional activity are identified